Kinetics of Micellar Catalyzed Oxidation of m-Cresol by Chloramine-T - Sarasan, Geetha (Asian Journal of Chemistry, 2011)
The effect of micelles formed from the surfactant, cetyl pyridinium bromide (CPBr) on the oxidation of m-cresol by chloramine-T has been investigated kinetically. More over the effect of mercuric acetate on the reaction rate in the presence and absence of the surfactant has also been investigated. It is observed that the rate of the reaction has a rapid enhancement in the presence of the surfactant, showing the micellar catalytic action of the surfactant. The effect of mercuric acetate is also enhancing. It is found that the action of the surfactant is affected by the presence of mercuric acetate. The effect of acetic acid concentration on the reaction rate has also been studied. Its effect is retarding. As we increase the acid strength, the rate of the reaction decreases. The effect of temperature on this reaction is also studied and the activation parameters like DE*, DH*, DS* and DG* are evaluated. The effect of [CAT], [m-cresol], has also been studied. From the results obtained, a plausible mechanism is suggested.